Pengembangan Media Flashcard Simulasi untuk Kosakata Ngoko dan Krama di SDN Sukorejo Tugu - Happy Nanda Asmara; Uswatun Hasanah (The Elementary Journal, 2026)
This research is based on the existence of problems in Javanese language learning in grade IV. Students consider the Javanese uploading material to be difficult material. Educators use the lecture method more, without the help of learning media so that students are bored. Therefore, the researcher developed a flashcard media for ngoko and krama vocabulary through a simulation method with the aim of helping students understand the differences and use of ngoko and krama vocabulary. This research uses the type (R&D) with the ADDIE model consisting of Analysis, Design, Development, Implementation, and Evaluation. The results of the study showed that (1) The development of flashcard media obtained 80% (valid) results from material expert validators, 97.3% (very valid) media expert validators, 96% (very valid) results from question validators. The results of the teacher trial were 100% (very good), the results of the small group trial were 86.7% (very good) and the results of the large group trial were 90.83% (very good). (2) The feasibility of flashcard media can be seen from the results of increasing pre-test to post-test scores. The average result of the pre-test score was 50.00 to 87.50 in the post-test results, so there was an increase of 37.50 points. This proves that the flashcard media of ngoko and krama vocabulary through the simulation method is declared suitable for use as a learning medium in Javanese language subjects in grade IV elementary school.